Controlling arms and terror in the Asia Pacific after Bali and Baghdad - Vicziany, Marika (Edward Elgar, 2007)
Years after 9/11, the Global War on Terror is still not over. The deepening crisis in Iraq has been accompanied by rising violence in Asia, as the bombings in Indonesia show. The 18 specialists and policymakers who have contributed to this book assess how the security scenario in the Asia Pacific has changed in response to these events.